Nutrient Utilization and Milk Yield in Crossbred Cows Fed Lathyrus Straw Supplemented Diet - Das, M M (Indian Journal of Animal Nutrition, 2021)
Lathyrus straw (LS) was supplemented to lactating crossbred cows weighing 370.7Â±10.42 kg to study the influence on nutrient intake, utilization and milk yield performance of the animals. In the control group (G1), the animals were fed wheat straw plus concentrate based ration whereas in the diet of G2 and G3 wheat straw was replaced with lathyrus straw at 30% and 50% on DM basis for 90 days. All the groups were provided iso-nitrogeneous diet. Intake of dry matter (DM) was 2.36, 2.38 and 2.21 of the body weight in groups G1, G2 and G3, respectively. Dry matter(DM) and fibre digestibility was comparable among the groups. However, digestibility of crude protein (CP) was significantly (P<0.05) higher (51.76%) in G1 or G2 (47.85%) as compared to G3 (44.98%). Milk yield and milk composition did not revealed any significant difference among the groups. The experimental results revealed that the feed cost per day was reduced significantly (P<0.05) from Rs. 103.98 to Rs.Â 92.68 and cost of feed per kg FCM was reduced from RsÂ 13.70 to12.12 in cows fed 50% LS straw supplemented diet as compared to control. Thus, Lathyrus straw can be safely incorporated in the ration of dairy animals for economic milk production without having any adverse effect on feed intake, nutrient utilization and production performance of crossbred cows.